Trans Subjectivity in Preciado’s Can the Monster Speak? : Limits and Possibilities of Preciado’s Engagement with Psychoanalysis - von Lupke, Lisa (My University, 2024)
In this thesis, I examine Paul B. Preciado’s speech Can the Monster Speak? (2019) and show how it reflects the ambivalent historical entwinement of psychoanalysis and trans*-ness. I suggest that Preciado uses the figure of the monster to articulate trans subjectivity, and that his conceptualisation of trans subjectivity is rooted in the refusal of and disidentification with normative discourses about trans lives. Through this refusal, Preciado illuminates the workings of these discourses. I read Preciado through postcolonial critiques in trans studies and show how Preciado’s strategies for making non-normative trans subjectivity visible risk becoming limiting due to an ambivalent attachment to psychoanalytic concepts and the colonial legacies in the psychoanalytic tradition. Finally, I connect the question of limitations in Preciado’s envisioned trans subjectivity to on-going discussions in trans studies over the field’s aims and object of study.
Keywords: trans subject, monstrosity, Paul B. Preciado, trans studies, subjectivity, psychoanalysis